Documenting design research by structured multilevel analysis: supporting the diversity of the design research community of practice. (6th January 2022) - Reich, Yoram; Subrahmanian, Eswaran
Abstract: The diversity of design research studies and their associated methods and reporting style make it difficult for the design research community of practice to leverage its work into further advancing the field. We illustrate how a structured multilevel analysis of diverse studies creates a canonical model that allows for the transfer of insight between studies, enhances their comprehension, and supports improved study designs. The benefits of such an approach will increase if different stakeholders adopt such structured approaches to enrich the design research community of practice.